The meanest man in Texas [videorecording (DVD)] - Ward, Justin (Director); Ward, Justin (Director); Ward, Mateus; Bard, Alexandra; McShane, Jamie; Umphrey, Don (Ammo Content, 2019)
The life of prisoner turned chaplain Clyde Thompson.